Thin film field-effect transistors of 2, 6-diphenyl anthracene (DPA)1. Issue 59 (28th July 2015) - Liu, Jie; Dong, Huanli; Wang, Zongrui; Ji, Deyang; Cheng, Changli; Geng, Hua; Zhang, Hantang; Zhen, Yonggang; Jiang, Lang; Fu, Hongbing; Bo, Zhishan; Chen, Wei; et al.
<x xml:space="preserve">Abstract</x> The present work showed the design, synthesis and characterization of a high performance anthracene-based semiconductor.